Does a measure of Medical Professional Identity Formation predict communication skills performance?. Issue 12 (December 2021) - Kalet, Adina; Ark, Tavinder K.; Monson, Verna; Song, Hyuksoon S.; Buckvar-Keltz, Lynn; Harnik, Victoria; Yingling, Sandra; Rivera, Rafael; Tewksbury, Linda; Lusk, Penelope; Crowe, Ruth
Abstract: Objective: To validate an approach to measuring professional identity formation (PIF), we explore if the Professional Identity Essay (PIE), a stage score measure of medical professional identity (PI), predicts clinical communication skills. Methods: Students completed the PIE during medical school orientation and a 3-case Objective Structured Clinical Exam (OSCE) where standardized patients reliably assessed communication skills in 5 domains. Using mediation analyses, relationships between PIE stage scores and communication skills were explored. Results: For the 351 (89%) consenting students, controlling for individual characteristics, there were increases in patient counseling (6.5%, p<0.01), information gathering (4.3%, p = 0.01), organization and management (4.1%, p = 0.02), patient assessment (3.6%, p = 0.04), and relationship development (3.5%, p = 0.03) skills for every half stage increase in PIE score. The communication skills of lower socio-economic status (SES) students are indirectly impacted by their slightly higher PIE stage scores. Conclusion: Higher PIE stage scores are associated with higher communication skills and lower SES. Practice implications: PIE predicts critical clinical skills and identifies how SES and other characteristics indirectly impact future clinical performance, providing validity evidence for using PIE as a tool in longitudinal formative academic coaching, program and curriculum evaluation, and research. Highlights: The Professional Identity Essay (PIE) provides a valid measure of a developmentally staged theory of Professional Identity formation in early medical students. PIE stage scores predict communication skills in 5 domains including and especially Patient Education. Students from lower socioeconomic status backgrounds have higher PIE stage scores on entry to medical school which mediate better communication skills. The PIE metric could be a valuable part of longitudinal, individualized academic coaching, curriculum and program evaluation and research.